The Qur’anic Worldview: A Springboard for Cultural Reform By AbdulHamid AbuSulayman (London: IIIT, 2011. 179 pages.) (American Journal of Islam and Society, 2013)
The thesis of this sophisticated book is that the rebirth of an Islamic identitycan only be realized through a decisive replication of the Muslim communitycreated through strict adherence to and implementation of the Qur’anic worldview.The specific details provided by AbdulHamid AbuSulayman in his attemptto present this thesis as credible and worthy of merit invariably exposethe work as one of synthesis and the lifetime project of an intellectual who isbeing propelled by his wanderlust for paving the way for the Muslims’ returnto the golden age of the Islamic heritage. For instance, he describes this bookas his “extended reflection on the Islamic worldview” (p. xv), around whichhis scholarship and personal experience have revolved. He also cites this reflectionas the reason why he has “grappled with … issues” relating to it fromhis early days and has continued to promote the same line of thought throughouthis “writing career that extended half a century” (p. xx).The book is divided into five chapters. In chapter 1, the author discussesthe relationship between the Qur’anic worldview and human nature. He baseshis argument on the premise that “every cultural system is associated with anunderlying worldview which is translated into action by means of a particular ...